Upaya Guru Mengatasi Siswa yang Mengalami Kesulitan Membaca dan Menulis di Kelas 5 MIN 1 Gresik - Muhammad Nizar Ibrahim; Muhammad Bahri Musthofa; Zudan Rosyidi; Muifah Muifah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Difficulty reading and writing is still a fundamental problem for some elementary school students, even though these two abilities are an important foundation in understanding various subjects. In the context of madrasah ibtidaiyah education, teachers play a strategic role in helping students overcome literacy barriers in order to be able to achieve basic competencies optimally. This study aims to describe the efforts of teachers in overcoming reading and writing difficulties experienced by three 5th grade students at MIN 1 Gresik. The research method uses a descriptive qualitative approach with observation, interview, and documentation techniques. The research subjects included grade 5 teachers and three students who experienced literacy barriers. The results of the study showed that teachers carried out various strategies, including adding special tutoring hours outside of regular learning, providing gradual exercises according to students' abilities, and utilizing visual media and educational games to increase learning motivation. Teachers also apply an individualized approach so that students are more focused and confident. In addition, parental involvement is optimized through intensive communication so that reading and writing exercises can continue at home. The obstacles faced include time constraints, differences in basic abilities, and low student concentration. Nevertheless, the perseverance and creativity of teachers have proven to be able to drive significant progress in the development of students' basic literacy.